Leukocyte recruitment in vivo - Kubes, Paul (Henry Stewart Talks, 2009)
Leukocyte recruitmen, A multi-step recruitment that involves rolling adhesion, crawling to junctions and emigration, Role of selectins and integrin subunits in this process, Role for other adhesion molecules in liver, lung and potentially other organs, Constitutive patrolling of immune cells in various tissues, Role for sentinel cells such as endothelium, mast cells and macrophage in inducing recruitment into tissues